CONCERTO NO.1 FOR VIOLIN AND CHAMBER ORCHESTRA BY OLEG NEGRUȚA: PECULIARITIES OF THE COMPOSITION AND MUSICAL LANGUAGE - BURUNOVA, ANASTASIA; BEREZOVICOVA, TATIANA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică)
The article is dedicated to one of Oleg Negruța’s instrumental concertos, namely Concerto no. 1 for violin and chamber orchestra. The formation of the composer’s creative ideas is often dictated by the needs of artistic practice: most of his compositions are part of the pedagogical repertoire of music schools (especially the Alexei Stârcea Art School), high schools, colleges and institutions of higher musical education, they are included in the programs of interpretation competitions and in the concert ones. The study of O. Negruța’s instrumental concertos is relevant not only because of their own artistic value, but also from the perspective of analyzing the more general processes of the historical development of musical art in the Republic of Moldova. Although the number of concertos in O. Negruță’s compositional repertoire is significant, it cannot be said that they have attracted enough attention from musicologists. Thus, the incentive to address this topic was not only the brilliant results of the composer’s artistic activity and the awareness of the significance of his creative experiences, but also the tendency to cover some gaps in the musicological study of O. Negruța’s work, in particular, his concertos for violin and orchestra.